Platform food delivery: a study on the labour process and emotional labour experienced by gig workers in the Eastern Cape food delivery sector - Mutshewa, Taboka Botsang (Rhodes University, Faculty of Humanities, Department of Sociology)
As central to the gig economy, digital platforms are transforming the character of the modern economy. South Africa has seen the increased use of technology and the integration of technological changes into the labour market and labour process, including via digital platforms. The gig economy has entered a range of economic sectors in South Africa and elsewhere, including the service sector. Examples of digital platforms in this specific sector include Uber and Bolt for transportation, Sweep South for domestic help, and Mr D Food for food delivery. Undoubtedly, by inhibiting and sanctioning movements globally and locally, the COVID-19 pandemic contributed to the expansion of the gig economy in the service sector, as it restricted walk-in customers. The digital platform mediates the relationship between service sector workers and their clients and between workers and the companies operating the platforms. In this way, these technological platforms act as an 'extra hand' by, for example, hiring delivery workers in the first instance and then facilitating the delivery of products to customers. This thesis examines the food delivery sector in the gig economy in the Eastern Cape Province of South Africa. The digital platforms in the food sector allow consumers to place food orders at a restaurant of choice and deliver them to their doorstep in less than an hour, ensuring convenience, reliability and efficiency for restaurants and customers. However, understanding the gig economy involves identifying and unpacking the experiences and perspectives of the gig workers. In doing so, this thesis examines food delivery workers labouring for two different companies (Uber East and Mr D Foods) in two sites (Makhanda and Gqeberha). The main aim is to analyse how the digital platforms restructure the labour process in the gig economy and the emotional labour enacted by the delivery workers. The thesis draws upon labour process and emotional labour theory to pursue this primary aim. Research findings highlight a high level of precariousness and stress amongst food delivery workers as they work under algorithmic systems of labour control marked by surveillance and are constantly required to perform emotionally to maximise income.
Keywords: Food delivery services -- South Africa -- Makhanda; Gig worker; Gig economy; Labor process theory; Emotional labor